PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PAPAN DIAGRAM UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS 5 DALAM PENYAJIAN DATA - Dwi Rusita Sari; Ulhaq Zuhdi; Ana Sofiya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to improve the understanding of grade 5 students about data presentation by using the Problem Based Learning (PBL) approach supported by diagramboard media. The background of this research is students' poor understanding of data presentation, which is characterized by their difficulty in understanding and presenting data in formats such as tables, graphs, and diagrams. This research is a second-class action research cycle. The first cycle involves the use of a problem-based learning (PBL) approach with the help of diagramboard media, and the second cycle is an improvement from the first cycle based on reflection carried out. The data collection methods carried out are observation, tests, and interviews. The data were analyzed in a qualitative and quantitative descriptive manner. The results of the study show that using the PBL approach with the help of diagramboard media can help 5th grade students understand data presentation better. The percentage of student learning completion in the first cycle was 67%, and increased to 86% in the second cycle. In addition, students' activity and their enthusiasm for learning have also increased significantly from category “quite active” in the first cycle to “very active” in the second cycle. Students are more skilled in presenting data and are more actively involved in the problem-solving process.